Research on Consumption Level of Rural Residents Using the Sustainable Livelihoods Framework - Beibei Li (Forest Chemicals Review, 1970)
From poverty alleviation to rural revitalization, the living conditions of rural residents in poverty-stricken areas have undergone earth-shaking changes. Consolidating such achievements is an important content of our country's future poverty alleviation work. Under the framework of sustainable livelihoods, this paper uses the generalized least squares (GLS) method to analyze the consumption level of rural residents in poverty-stricken areas from the aspects of natural capital, physical capital, and social capital. The research shows that the natural capital, physical capital, human capital, financial capital and psychological capital in the livelihood capital of rural residents have a significant positive impact on their consumption level, but the social capital has no significant impact on the consumption level.